Green mechanical evaluation of mullite porous compacts prepared by pre-gelling starch consolidation - Talou, Mariano Hernán (2012)
The mechanical behavior of green porous mullite disks (volume porosity > 55%) prepared by the thermogelation of mullite aqueous suspensions with different native starches (i.e. potato, cassava and corn starches) was studied. One set of disks was prepared by thermal consolidation (70–80 °C, 2 h) of aqueous mullite suspensions (40 vol.%) containing 10 vol.% of starch pre-gelled at 55–60 °C and dried at 40 °C for 24 h. Another set of specimens was prepared by additional firing at 650 °C for 2 h to burn-out the starches. Both sets of disks were characterized by density measurements (Archimedes method), apparent porosity calculus, and microstructural analysis by SEM. Mechanical parameters such as fracture strength, apparent elastic modulus, fracture and final deformations and yield stress were determined from apparent stress–strain relations derived from load-displacement curves obtained by diametral compression testing. Moreover, typical crack patterns were evaluated and fractographic analysis was carried out by SEM. Mechanical results were analyzed in relation to the behavior of the starches in aqueous suspension and the properties of the developed gels, together with the respective microstructures before and after the burn-out process. Mechanical data were also considered taking into account the possibility of machining the green compacts formed by pre-gelling starch consolidation.